(untitled) (International Journal of Engineering and Computer Science, 2014)
Image Compression is a method, which reduces the size of the data or the amount of space required to store the data. Digital image in their raw form require an enormous amount of storage capacity. There are various transformation techniques used for data compression. Discrete Cosine Transform (DCT) and Discrete Wavelet Transform (DWT) are the most commonly used transformation.The Discrete cosine transform (DCT) is a method for transform a signal or image from spatial domain to frequency component. DCT has high energy compaction property and requires less computational resources. On the other hand, DWT is multi resolution transformation. In this paper, we propose a mixed DWT-DCT algorithm for image compression and reconstruction taking benefit from the advantages of both algorithms.